2013
DOI: 10.1590/s0103-84782013005000080
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa do potencial produtivo em trigo utilizando sensor óptico ativo para adubação nitrogenada em taxa variável

Abstract: RESUMO A adubação nitrogenada em trigo é baseada no potencial produtivo da cultura, teor de matéria orgânica do solo e cultura antecessora. A defi nição do potencial produtivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
0
22
0
10
Order By: Relevance
“…Thus, the adjustment of an adequate dose, regardless of the condition of the year and N-fertilizer, can qualify the guarantee of recommendation of this technology. In the plant, the N-fertilizer stimulates vegetative and root growth, with reflex in the absorption of nutrients and production of biomass and grains (Flores et al, 2012); however, nitrogen, along with the favorable meteorological conditions, acts on plant lodging (Bredemeier et al, 2013). Benin et al (2012) and Prando et al (2013) observed, in wheat, that the increment in the N-fertilizer dose favors plant lodging, especially in rainy years.…”
Section: Bmentioning
confidence: 99%
“…Thus, the adjustment of an adequate dose, regardless of the condition of the year and N-fertilizer, can qualify the guarantee of recommendation of this technology. In the plant, the N-fertilizer stimulates vegetative and root growth, with reflex in the absorption of nutrients and production of biomass and grains (Flores et al, 2012); however, nitrogen, along with the favorable meteorological conditions, acts on plant lodging (Bredemeier et al, 2013). Benin et al (2012) and Prando et al (2013) observed, in wheat, that the increment in the N-fertilizer dose favors plant lodging, especially in rainy years.…”
Section: Bmentioning
confidence: 99%
“…Defining management zones requires various steps, from data collection to map evaluation, based on which the cultivation area is divided into subareas that have homogeneity with respect to the evaluated attributes (RODRIGUES; CORÁ; FERNANDES, 2012;ALVES et al, 2013;FARID et al, 2013;DALCHIAVON et al, 2013;BAZZI et al, 2015;SANTOS et al, 2015;SARAIVA, 2015). This allows the application of inputs at appropriate rates for improving the productivity of a crop (BREDEMEIER et al, 2013;BAGHERI et al, 2013;COSTA et al, 2014). However, it is common to see variations in sampling methods, laboratory analyses, statistics, and geostatistics, irrespective of their correlation with plant productivity (ALVES et al 2013;BREDEMEIER et al, 2013;URRETAVIZCAYA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This allows the application of inputs at appropriate rates for improving the productivity of a crop (BREDEMEIER et al, 2013;BAGHERI et al, 2013;COSTA et al, 2014). However, it is common to see variations in sampling methods, laboratory analyses, statistics, and geostatistics, irrespective of their correlation with plant productivity (ALVES et al 2013;BREDEMEIER et al, 2013;URRETAVIZCAYA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the appropriate time for nitrogen topdressing is defined by the plant phenology, according to the period of greatest deficiency of the nutrient during plant development and formation of yield components (Bredemeier et al, 2013). The periods when wheat mostly requires nitrogen is from the emergence until the sixth leaf stage (Yano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%